N-(4-Bromophenyl)-2-(2-thienyl)acetamide - Nogueira, T.C.M.; de Souza, M.V.N.; Wardell, J.L.; Wardell, S.M.S.V.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The thienyl ring in the title compound, C(12)H(10)BrNOS, is disordered over two diagonally opposite positions, the major component having a site-occupancy factor of 0.660 (5). The molecule is twisted as evidenced by the dihedral angles of 70.0 (4) and 70.5 (6)degrees formed between the benzene ring and the two orientations of the disordered thiophene ring. Linear supramolecular chains along the a axis are found in the crystal structure through the agency of N-H center dot center dot center dot O hydrogen bonding.